Congenital Y-urethra: a diagnostic and therapeutic challenge - Lorenz, Christian; Zahn, Katrin; Schäfer, Frank-Mattias; Möller, Kristina; Stehr, Maximilian; Stein, Raimund (Journal of pediatric urology, 2021)
Background - For the Y-subtype of urethral duplications expression and nomenclature vary, as treatment recommendations do. - Objective - To raise awareness of the variety and variable terminology of Y-type duplication of the urethra, and to discuss the diagnostic work-up in light of options for or against surgical reconstruction. - Materials and methods - Five patients with congenital Y-urethra were treated in four institutions within 15 years (2004-2019). While patients were managed in our respective institution with some exchange of experience, all available data were shared and evaluated for this review. - Results - The age at initial presentation was 1 day-6 months. In three patients the Y-urethra was found together with an anorectal malformation (ARM). With the focus on reconstruction rather than suprapubic diversion the orthotopic urethra was restored in the majority of patients using either single-step or staged approaches while the accessory urethral limb was incorporated. This was successful despite additional procedures aiming at ARM reconstruction. The patients void spontaneously and do control urine and bowels. One patient underwent kidney transplantation as a consequence of associated renal anomalies while reconstructive attempts regarding his urethral anomaly failed. In two patients, uncertainty in recognizing the pathology delayed a purposive treatment. - Discussion - For this rare anomaly the terminology in the literature merges and suggestions for the treatment differ. Success in four out five patients supports an approach which makes use of the accessory ventral track to restore the orthotopic urethra. Since some patients present as a neonatal emergency with concomitant problems such as ARM, a basic understanding of the variable pathology is required. - Conclusion - The cases of Y-urethra reported herein demonstrate that correct allocation at the initial presentation or at least prior to first surgical steps will preserve the chance for physiologic micturition and urinary continence. Timing of surgery has to be done in the context of associated malformations and is not an emergency as long as proper bladder drainage is ensured. However, relocation of the accessory track requires several procedures bearing risks of complications short and long-term. This may be an argument to consider any therapeutic strategy against other options such as postponed treatment or permanent suprapubic diversion. Evidence-based guidelines are lacking.